Material-Based Engineering Strategies for Cardiac Regeneration - H. van Marion, Mieke; A.M. Bax, Noortje; C.C. van Spreeuwel, Ariane; W.J. van der Schaft, Daisy; V.C. Bouten, Carlijn (Current Pharmaceutical Design, 2014)
Cardiac tissue is composed of muscle and non-muscle cells, surrounded by extracellular matrix (ECM) and spatially organized into a complex three-dimensional (3D) architecture to allow for coordinated contraction and electrical pulse propagation. Despite emerging evidence for cardiomyocyte turnover in mammalian hearts, the regenerative capacity of human cardiac tissue is insufficient to recover from damage, e.g. resulting from myocardial infarction (MI). Instead, the heart ‘repairs’ lost or injured tissue by ongoing synthesis and remodeling of scar tissue. Conventional therapies and timely (stem) cell delivery to the injured tissue markedly improve short-term function and remodeling, but do not attenuate later stage adverse remodeling, leading to functional deterioration and eventually failure of the heart. Material-based therapies have been successfully used to mechanically support and constrain the post-MI failing heart, preventing it from further remodeling and dilation. When designed to deliver the right microenvironment for endogenous or exogenous cells, as well as the mechanical and topological cues to guide neo-tissue formation, material-based therapies may even reverse remodeling and boost cardiac regeneration. This paper reviews the up-to-date status of material-based cardiac regeneration with special emphasis on 1) the use of bare biomaterials to deliver passive constraints that unload the heart, 2) the use of materials and cells to create engineered cardiac constructs for replacement, support, or regeneration of damaged myocardium, and 3) the development of bio-inspired and bioactive materials that aim to enhance the endogenous regenerative capacity of the heart. As the therapies should function in the infarcted heart, the damaged host environment and engineered in vitro test systems that mimic this environment, are reviewed as well.
Keywords: stem cells